2020
DOI: 10.2147/ott.s256336
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNA GATA6-AS1 Sponges miR-324-5p to Inhibit Lung Cancer Cell Proliferation and Invasion</p>

Abstract: Background: Long non-coding RNAs (lncRNAs), which are key regulators of gene expression, are involved in lung cancer progression. Although numerous differentially expressed lncRNAs have been reported, merely a limited number of studies have been performed to verify their functions in lung cancer. Methods: RNA sequencing data were re-analyzed to investigate the GATA6-AS1 expression in lung cancer. RT-qPCR was performed to verify the expression of GATA6-AS1 in collected tissue samples and cell lines. CCK-8 and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
2
Order By: Relevance
“…Overall, these findings exhibited that GATA6-AS1 exerted tumor suppressive function in the cellular processes of LUAD. Previously, GATA6-AS1 was indicated to suppress proliferation and migration of LUAD cells by binding with miR-543 to upregulate RKIP [ 36 ] and by sponging miR-324-5p to increase the expression of FBXO11 and SP1 [ 37 ]. GATA6-AS1 is associated with the favorable prognosis of lung squamous cell carcinoma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings exhibited that GATA6-AS1 exerted tumor suppressive function in the cellular processes of LUAD. Previously, GATA6-AS1 was indicated to suppress proliferation and migration of LUAD cells by binding with miR-543 to upregulate RKIP [ 36 ] and by sponging miR-324-5p to increase the expression of FBXO11 and SP1 [ 37 ]. GATA6-AS1 is associated with the favorable prognosis of lung squamous cell carcinoma [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GATA6-AS1 lncRNA has been linked to the expression of F-box proteins [85], which play an important role in the degradation of key proteins in cellular regulation and tumorigenesis [86]. It has been studied in the context of lung, gastric, and ovarian cancer in association with the inhibition of signaling pathways and prevention of epithelialmesenchymal transition [87,88]. The hub gene GATA6-AS1 was in the green cluster and had 26 interactions.…”
Section: Gene Expression Of Stromal Cells In Breast Tumors Is Related...mentioning
confidence: 99%
“…LincRNA GATA6-AS1 promoted GATA6 expression and controlled the behaviors of lung cancer cells ( 146 ). In lung cancer cells, lincRNA GATA6-AS1 suppressed cell proliferation and invasive ability ( 147 ). Using several approaches, including RNA sequencing dataset, RT-qPCR and TCGA data, one group found that GATA6-AS1 expression levels were downregulated in lung cancer tissues ( 147 ).…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%
“…In lung cancer cells, lincRNA GATA6-AS1 suppressed cell proliferation and invasive ability ( 147 ). Using several approaches, including RNA sequencing dataset, RT-qPCR and TCGA data, one group found that GATA6-AS1 expression levels were downregulated in lung cancer tissues ( 147 ). Moreover, GATA6-AS1 overexpression increased the expression of FBXO11 and SP1 via sponging miR-324-5p, contributing to enhancement of invasion and proliferation in lung cancer cells.…”
Section: Lncrnas Regulate the Expression Of F-box Proteinsmentioning
confidence: 99%
See 1 more Smart Citation